QUALITY OF INTERPERSONAL COMMUNICATION IN ABUSIVE RELATIONSHIP - Muhammad Saifulloh; Adiella Yankie Lubis; Eni Kardi Wiyati; Shannon Aurelia (Universitas prof. Dr. Moestopo (Beragama), 2022)
This research looks at how communication can help victims of abusive relationships maintain their relationships. The goal of this study is to first figure out how victims can stay in abusive relationships, and then to figure out how victims' experiences in abusive relationships are described. The notion of Interpersonal Communication and the theory of Relationship Maintenance were applied in this study. This research employed a phenomenological method and a qualitative approach with a constructivism paradigm. The information was gathered by interviews or in-depth interviews with four sources, and the results were assessed using the source triangulation data validity technique. The findings revealed that relationship violence can take many forms, including physical, emotional, sexual, and financial. During and after the occurrence of violence, abusive relationships tend to go through cycles. Even though they are in an abusive relationship, the perpetrator still engages in relationship maintenance behaviors such as giving praise, being open to each other, providing certainty in relationships, doing tasks together, and interacting with others, as stated in the relationship maintenance theory. Victims of abusive relationships have their own reasons for staying in abusive relationships, such as the fact that they have been in an abusive relationship for a long time, still love them, and are frightened to leave.